Mapping Murine Diabetic Kidney Disease Using Chemical Exchange Saturation Transfer MRI - Wang, Feng (Magn Reson Med, 2015)
INTRODUCTION: Diabetic nephropathy (DN) is the leading cause of renal failure; however, current clinical tests are insufficient for assessing this disease. DN is associated with changes in renal metabolites, so we evaluated the utility of chemical exchange saturation transfer (CEST) imaging to detect changes characteristic of this disease. METHODS: Sensitivity of CEST imaging at 7T to DN was evaluated by imaging diabetic mice (db/db, db/db eNOS−/−) that show different levels of nephropathy as well as by longitudinal imaging (8 to 24 weeks). Non-diabetic (db/m) mice were used as controls. RESULTS: Compared with non-diabetic mice, the CEST contrasts of hydroxyl metabolites that correspond to glucose and glycogen were significantly increased in papilla (P), inner medulla (IM), and outer medulla (OM) in db/db and db/db eNOS−/− kidneys at 16 wks. The db/db eNOS−/− mice that showed advanced nephropathy exhibited greater CEST effects in OM and significant CEST contrasts were also observed in cortex. Longitudinally, db/db mice exhibited progressive increases in hydroxyl signals in IM+P and OM from 12 to 24 weeks and an increase was also observed in cortex at 24 weeks. CONCLUSIONS: CEST MRI can be used to measure changes of hydroxyl metabolites in kidney during progression of DN.